Primary Pancreatic Neuroblastoma in an Infant. Issue 6 (August 2020) - Morrison, Zachary D.; Sun, Yeping; Manalang, Michelle; Dominguez, Kathleen
Abstract : A 2-month-old girl with conjugated hyperbilirubinemia was found at the surgery and by computed tomography to have a large mass originating in the pancreas. Histopathology, molecular testing, and staging evaluations showed this to be a stage 3, MYCN unamplified, intermediate-risk neuroblastoma. The patient had a partial response to risk-stratified chemotherapy. The mass remained unresectable, but the response was sustained after 18 months. Although fewer than a dozen cases of primary pancreatic neuroblastoma have been reported, our experience and a literature review suggest that these tumors can be managed in the same way as similar-risk neuroblastoma of other sites.